Organizational theory, design, and change - Jones, Gareth R. (Pearson/Prentice Hall, 2007)
Organizational theory, design and change is the only text that brings together coverage of organizational theory and organizational change to allow faculty to teach how org. theories are put into practice for analyzing and changing organizations.